Sewage Waste and Treatment Plants Case Study: Beit Lahia Plant-North Gaza Strip - Al-Ashqar, Mahmoud; Muslim, Alaa Mahmoud; Mohammed, Khaldoon (Journal of Risk and Crisis Management, 2019)
The study aims to identify the importance of wastewater treatment on the surrounding environment. The case study was the North Plant in the village of Umm Al-Nasr (Gaza Strip). The study aims also to identify the plant role in the wastewater treatment sector in the governorate of North Gaza Strip, identify the difficulties and risks facing the work of the plant and also determine the planning requirements for emergency response at the North Water Treatment Plant. The researchers suggested response procedures in case of emergency events of the sewage system in Northern Gaza Strip. The researchers followed the descriptive analytical approach of the information sources and reports issued by the institutions related to the sewage stations in the Gaza Strip. The study also included field visits to the North Plant and employee interviews to study the stages of treatment and disposal methods of sludge. The study recommended the need to work on the development of the emergency of North Plant Project in order to accommodate the increase in the quantities of treated water, as well as working on an emergency plan to deal with potential hazards in addition preparedness and response procedures for each expected case.